(2x-1)2+(2x+1)2-2(2x+1)(2x-1)+x=12
=> (2x+1)2-2(2x+1)(2x-1)+(2x-1)2+x=12
=>[(2x+1)2-2(2x+1)(2x-1)+(2x-1)2 ]+x=12
=>[(2x+1)-(2x-1)]2+x=12
=>(2x+1-2x+1)2+x=12
=>22+x=12
=>4+x=12
=>x=8
vậy x=8
(2x-1)2+(2x+1)2-2(2x+1)(2x-1)+x=12
=> (2x+1)2-2(2x+1)(2x-1)+(2x-1)2+x=12
=>[(2x+1)2-2(2x+1)(2x-1)+(2x-1)2 ]+x=12
=>[(2x+1)-(2x-1)]2+x=12
=>(2x+1-2x+1)2+x=12
=>22+x=12
=>4+x=12
=>x=8
vậy x=8
Tìm x)
x(1-2x) +(x-2).(2x-3) = 0
x(2x -4) -2x (x+3) =0
(2x+3)2+(x-3).(2x+3) =0
10y2 -2xy +25 +x2 +30y
(2x-1)2 +(2x+1)2 -2(2x-2)(2x+1) +x = 12
Giải các phương trình :
a) (2x + 5)2 = (x + 2)2
b) 2x3 + 6x2 = x2 + 3
c) 1 + 1/x +2 = 12/ 8 - x3
d) 2(1-2x)/4 - 2 + 3x/6 = 2 - 2(3x -1)/ 2
e) (x - 2)(2x - 3) = (4 - 2x)(x - 2)
f) 2x( x - 3) + 5(x - 3) = 0
g) 4x2 - 1 = (2x + 1)(3x - 5)
Giải các phương trình sau:
a) (2x-1)2-(3x+5)(2x-1)=0
b)\(\dfrac{x+5}{4}-\dfrac{2x-3}{3}=\dfrac{2x-1}{12}\)
c)\(\dfrac{x+1}{x-1}-\dfrac{x-1}{x+1}=\dfrac{-4}{1-x^2}\)
d)\(\dfrac{1}{x+1}+\dfrac{2x-1}{x^3+1}=\dfrac{2}{x^2-x+1}\)
Câu 1. Giải các phườn trình sau:
a, 3x+6=0
b, 2x-10=0
c, 3x-7=11
d, 3x-9=0
e, 3x(2-x) =15(x-2)
f, (x+5)(x+4)=0
g, x(x+4)=0
h, (2x -4)(x-2)=0
i, (x+1/5)(2x-3)=0
k, x²-4x=0
m, 4x²-1=0
n, x²-6x+9=0
l, (3x-5)²-(x+4)²=0
o, 7x(x+2)-5(x+2)=0
p, 3x(2x-5)-4x+10=0
q, (2-2x)-x²+1=0
r, x(1-3x)=5(1-3x)
s, 2x-3/4+x+1/6=3
t, x-3/4-2x+1/3=x/6
u, x+1/13+x+2/12=x+3/11+x+4/10
v, 2x+1/15+2x+2/14=2x+3/13+2x+4/12
Giúp e nha mn. E cảm ơn trc ạ!
1) x ² + 2x -4 = -12 + 3x + x ²
2) x( 2x - 3 ) - x ² + 2 = x(x - 5) - 1
3) (x-1)(x+3) = x² -4
4) (6x + 2)(x-2) = 2x(3x-5)
5) (x-2) ² = (x-3)(x+2)
Giải các phương trình sau
a) |x-2| = 3
b) |x+1| = |2x+3|
c) |3x| = x+6
d) |x-5| = 13-2x
e) |5x-1| = x-12
f) |-2x| = 3x+4
g) |2x-1| = 6-x
h) |-1+5x| = 8-x
i) |-2x+1| = x+3
k) |-2-5x| = -4x+7
1.giải pt
a)\(\dfrac{16-x}{4}=\dfrac{2x+1}{3}\)
b)(2x+3)(1-3x)=9x\(^2\)-1
c)\(\dfrac{2x}{x+1}+\dfrac{x-1}{x}=\dfrac{2x^2+3x-1}{x^2+x}\)
a,\(\dfrac{x^3+2x}{x^3+1}+\dfrac{2x}{x^2-x+1}+\dfrac{1}{x+1}\)
b,\(\dfrac{1-3x}{2x}+\dfrac{3x-2}{2x-1}+\dfrac{3x-2}{2x-4x^2}\)
a) x-1/x+1/x+1=2x-1/x^2+x
b) 5/x-3-2x-3/x+3=2x(1-x)/x^2-9